Pengaruh Self-Efficacy dan Metakognitif Self-Regulation Terhadap Kemampuan Berpikir Kritis Siswa SMA Negeri 10 Malang - Huda, Nuril; Watung, Sjeddie Rianne; Faresi, Gilang Muhammad Fajri; Laratmase, Antonia Junianty; Patty, Jusak (Cetta: Jurnal Ilmu Pendidikan, 2024)
Critical thinking ability is an essential skill that students need to have to face challenges in solving problems in the modern world. This research analyzes the influence of metacognitive self-regulation and self-efficacy on students' critical thinking skills at SMK Negeri 10 Malang. A sample of 72 students was selected using non-probability techniques to describe variable relationships in detail. The research results show that there is a significant correlation between self-efficacy and metacognitive self-regulation on students' critical thinking skills, where self-efficacy has a negative impact on these skills, while metacognitive self-regulation has a significant positive impact. Statistical testing shows a significance value of 0.000 with Fcount of 63.914, greater than Ftable 3.13, indicating the simultaneous influence of the two variables on students' critical thinking skills. These results provide a new perspective on the importance of approaches that encourage students to manage their thinking processes independently and purposefully. An emphasis on metacognitive self-regulation appears to be effective in establishing better critical thinking skills, while the negative impact of too high self-efficacy indicates the need for balance in learning. These findings lead to the understanding that the development of critical skills can be achieved more optimally when students are directed not only to rely on self-confidence, but also pay attention to managing their thinking processes.